Memahami dan Menanggulangi Persoalan Ketimpangan Agraria (1) - M Shohibuddin (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2019)
Abstract: This article offers two contribution to literature on agrarian inequality in Indonesia, namely a conceptual approach for understanding this phenomenon and its implication on policy formulation. The first contribution includes a synthesis of some literature on various aspects of agrarian inequality. In addition, two types of agrarian inequality are distinguished according to its locus of existence, i.e. inequality of distribution which refers to unequal land tenure among different classes within smallholding agricultural sector, and inequality of allocation which refers to unequal allocation of land and other natural resources between small (family) farms and large (corporate) enterprises. The second contribution is formulation of a policy framework to resolve these two types of agrarian inequality. First of all, the politics of agrarian resources allocation should be based on the principle of positive discrimination which favors smallholders’ interests. Furthermore, to ensure this principle comes into reality, five schemes of tenure reform have to be fully integrated, namely: (re)distribution, registration, recognition, devolution and restitution. This article divided into two parts. Part 1 will focus on the first contribution (conceptual approach); meanwhile, the second contribution (policy formulation) will be further elaborated in Part 2.Keywords: agrarian inequality, land reform, politics of agrarian resources allocation, Indonesia.Intisari: Dua kontribusi diajukan artikel ini pada kepustakaan mengenai ketimpangan agraria di Indonesia, yaitu pendekatan konseptual untuk memahami gejala ketimpangan agraria ini dan implikasinya pada penyusunan kebijakan. Kontribusi pertama mencakup sintesis atas sejumlah literatur mengenai berbagai aspek ketimpangan agraria. Selain itu, dua jenis ketimpangan agraria juga dibedakan berdasarkan locus keberadaanya, yaitu ketimpangan distribusi yang berarti kesenjangan penguasaan tanah di antara berbagai kelas dalam sektor pertanian rakyat, dan ketimpangan alokasi yang berarti kesenjangan peruntukan tanah dan sumber daya alam lain antara usaha tani skala kecil (keluarga) dengan usaha skala besar (korporasi). Kontribusi yang kedua adalah formulasi suatu kerangka kebijakan untuk menanggulangi dua jenis ketimpangan agraria di atas. Pertama-tama, politik alokasi sumber-sumber agraria harus didasarkan pada prinsip diskriminasi positif yang memihak kepentingan produsen kecil. Lalu, agar prinsip ini bisa terwujud di dunia nyata, lima skema pembaruan tenurial berikut ini mesti diintegrasikan secara menyeluruh, yaitu: (re)distribusi, registrasi, rekognisi, devolusi dan restitusi. Artikel ini terbagi menjadi dua bagian. Bagian 1 akan membahas kontribusi yang pertama (pendekatan konseptual), sementara kontribusi yang kedua (formulasi kebijakan) akan dielaborasi lebih lanjut pada Bagian 2.Kata Kunci: ketimpangan agraria, land reform, politik alokasi sumber-sumber agraria, Indonesia.